2015
DOI: 10.1212/wnl.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Brain amyloidosis ascertainment from cognitive, imaging, and peripheral blood protein measures

Abstract: This study provides Class II evidence that a classification algorithm based on cognitive, imaging, and peripheral blood protein measures identifies patients with brain amyloid on PiB-PET with moderate accuracy (sensitivity 68%, specificity 78%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…This is likely because measuring Aβ deposition can be expensive and requires either access to a PET facility (amyloid PET) or experience in performing lumbar puncture, which is regarded as an invasive procedure (CSF Aβ). Further, proxy measures of Aβ based on peripheral blood proteins, which would be less costly and invasive, are not yet able to definitively identify abnormal Aβ levels[42]. A pathway-specific PRS could be used to identify patients with a higher genetic risk of having elevated Aβ deposits who may be candidates for Aβ accumulation screening.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because measuring Aβ deposition can be expensive and requires either access to a PET facility (amyloid PET) or experience in performing lumbar puncture, which is regarded as an invasive procedure (CSF Aβ). Further, proxy measures of Aβ based on peripheral blood proteins, which would be less costly and invasive, are not yet able to definitively identify abnormal Aβ levels[42]. A pathway-specific PRS could be used to identify patients with a higher genetic risk of having elevated Aβ deposits who may be candidates for Aβ accumulation screening.…”
Section: Discussionmentioning
confidence: 99%
“…Kiddle et al similarly reported a signature that was associated with neocortical Aβ deposition, identifying 13 markers which were able to explain over 30 % of the between subject variation observed in neocortical Aβ deposition [60]. Other studies with the same aim of inferring neocortical Aβ deposition from a blood biomarker signature have reported efficacies of between 58 and 78% [61][62][63]. A replication study by Voyle and colleagues found pancreatic polypeptide and IgM to correlate with neocortical Aβ deposition, with IgM also correlating with neocortical Aβ deposition within cognitively normal participants [63].…”
Section: Panels Of Blood-based Biomarker-associated Disease Phenotypesmentioning
confidence: 99%
“…The full texts of the remaining 40 publications were assessed for eligibility. A total of 28 studies were included in the qualitative synthesis of which 12 had a prospective study design [14, 16, 18, 19**, 20, 21, 22, 23, 24, 25**, 26, 27] and 16 had a cross-sectional design [28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43]. By hand search of reference lists and recent updates of included studies one additional publication was identified [44].…”
Section: Identification Of Study Reportsmentioning
confidence: 99%
“…Investigators of the ADNI cohort reported that plasma apoJ levels did not differ between individuals with MCI progressing to AD and individuals with MCI not progressing to AD [19**]. Although apoJ levels were significantly positively related to prevalent AD or all-cause dementia at baseline, apoJ levels did not predict incident all-cause dementia during 7 years of follow-up in the well-characterized population-based Rotterdam study [26].…”
Section: New Insights Into the Role Of Hdl-c And Apolipoproteins In Dmentioning
confidence: 99%